PEMBERIAN ASI EKSKUSIF DENGAN KEJADIAN ISPA PADA BALITA - Sriami .; Nolo Sulasmi; Luthfi Amri Rokhmi (JURNAL PENELITIAN KESEHATAN, 2015)
Acute Respiratory Infection ( ARI ) is one of the most common causes of death in children indeveloping countries. Acute respiratory tract infections have led to four of the 15 million estimate causesof death in children under 5 years of age. Factors - factors that affect the incidence of ARI among others,lack of nutrients, age 2 months, LBW, not breastfeeding adequate ( non- exclusive) , air pollution,environmental rundown, immunization, and devisiensi vitamin A. The purpose of this study was to analyzedifferences in the incidence of ARI in children aged 1-4 years between exclusively breastfed and nonbreastfedexclusively in poly child RSUHaji Surabaya .Analytic observational study ( cross-sectional ) . The location of research in child poly RSU HajiSurabaya 2 - May 31, 2011. Total population of 110 children with simple random sampling sampling asample size of 86 children . The independent variable is non- exclusive breastfeeding and exclusivebreastfeeding , being the dependent variable was the incidence of ARI . source data from medical recordsthat were tested by chi - square.The results showed almost entirely of children suffering from ARI ( 81.39 % ) received nonexclusivebreastfeeding . From Chi- Square obtained X2hitung ( 4.70 ) X2tabel ( 3.84 ) it can beconcluded that HOis rejected it means there is no difference in the incidence of ARI among children aged1-4 years who were breastfed exclusively with non- exclusive breastfeedingConclusion that there are differences in the incidence of respiratory infection in infants aged 1-4years between exclusively breastfed and non- breastfed exclusively. Infants who are exclusively breastfedtendency to ARI lower when compared to that received non- exclusive breastfeeding was suggested thatthe importance of exclusive breastfeeding .Keywords: ARI, exclusive breastfeeding / non- exclusive breastfeeding